Ultrasound-guided placement of a midline catheter in a patient with extensive postburn contractures: A Case report. Issue 3 (January 2019) - Yokota, Taisuke; Tokumine, Joho; Lefor, Alan Kawarai; Hasegawa, Ayako; Yorozu, Tomoko; Asao, Takayuki
Abstract: Rationale: Obtaining venous access in a patient with extensive postburn scar contractures is a challenge. Patient concerns: A 39-year-old woman suffered a burn 2 years previously with a total body surface area burn of 93%, and a burn index of 85. Reconstructive surgery was previously performed 39 times. Split-thickness skin grafting to the neck was planned. She had no accessible peripheral veins. Diagnosis: Difficult venous access due to excessive burn scar contractures. Interventions: Central venous catheterization was considered impossible even with ultrasound guidance. We placed a midline catheter for intraoperative venous access in a patient with extensive burn scar contractures. The midline catheter is a peripheral venous catheter placed in an arm vein. Outcomes: We successfully placed a midline catheter in the right brachial vein. This catheter was used for 24 days without difficulty. Lessons: The midline catheter is a viable choice in patients with difficult vascular access due to extensive postburn scar contractures.